Survey on Smart Pig for Inspection Robot - Kanniga, E.; Malik, Mohamed (International Journal of Psychosocial Rehabilitation, 2019)
Smart pigs are an aggregate of sophisticated electronic gadgets utilizing numerous technologies and encompass signal sources, sensors to discover numerous anomalies, onboard computer(s) to acquire and collect statistics, and power assets to pressure all the electronics. Together, this gadget installed on a pig sled can without difficulty exceed several heaps in weight, specifically the ones tools for large-diameter pipelines. The term “smart pig” is utilized to distinguish the equipment containing sophisticated electronics from more traditional run-in pipelines for numerous functions. Existing technologies for inspecting pipelines and different matters, including the human frame, are surveyed. A sensor that could document multiple kinds of information, along with temperature, pressure, and acceleration, and save them at the unit turned into selected and adapted for use in pipelines